Assessing immune aging in HIV-infected patients. Issue 5 (4th July 2017) - Appay, Victor; Sauce, Delphine
ABSTRACT: Many of the alterations that affect innate and adaptive immune cell compartments in HIV-infected patients are reminiscent of the process of immune aging, characteristic of old age. These alterations define the immunological age of individuals and are likely to participate to the decline of immune competence with HIV disease progression. It is therefore important to characterize these changes, which point toward the accumulation of highly differentiated immunocompetent cells, associated with overall telomere length shortening, as well as understanding their etiology, especially related to the impact of chronic immune activation. Particular attention should be given to the exhaustion of primary immune resources, including haematopoietic progenitors and naïve cells, which holds the key for effective hematopoiesis and immune response induction, respectively. The alteration of these compartments during HIV infection certainly represents the foundation of the immune parallel with aging.